Inovasi Model Pemanasan Secara Cerdas dalam Mendukung Terciptanya Jantung Sehat pada Posyandu Lansia - Fredericus Pramonodjati; Liss Dyah Dewi Arini; Anggraini Sih Prabandari; Nataly Ayu Utami; Selvina Dwi Rahmawati; Azizah Zahra Nur Fitria; Azzahra Nabilla Atha; David Valentino Iskandar; Erika Dwi Susanti; Nur Aini Fatna Fadilla (Lembaga Pengembangan Kinerja Dosen, 2025)
The “Sejahtera” Elderly Posyandu is one of the integrated health posts (Posyandu) fostered by the Jaten II Ngringo Community Health Center (UPT) in Jaten, Karanganyar. Ngringo is developing the “Ngudi Sehat” Quality Family Village, which focuses on improving the quality of life of families. In terms of health potential, the presence of the Mojosongo 2 Special Surgery Hospital, the Hajah Rodiah Maternity Hospital, and the Jaten 2 Community Health Center supports health services for the community. Ngringo has a strategic location, as the gateway to Karanganyar Regency, Ngringo has the potential to be a center for trade, distribution, and public services, and has supporting infrastructure such as markets, terminals, and flyovers to support economic activities and mobility. This community service model (method) uses 7 (seven) main activity stages, namely Identification of partner problems and needs, preparation of innovative materials and media, apperception, implementation of the Warming Model (counseling and training to posyandu cadres and the elderly, cooking healthy food for cadres and participants, simple health checks for cadres and participants, provision of simple health equipment), monitoring, evaluation and mentoring, documentation and reporting and termination. The results of this activity are The conclusion of the results of this PMP activity is. The output of this PMP is a PKM journal article indexed by Sinta 4 https://journalshub.org/index.php/JPIKes, Jawa Pos newspaper, activity videos and books.